Damage tolerance of nuclear graphite at elevated temperatures - Dong Liu (Nature Portfolio, 2017)
Nuclear-grade graphite is an important high-temperature structural material for fission reactors. Here, the authors perform simultaneous X-ray tomography and mechanical testing on a nuclear-grade graphite, finding simultaneous improvement of strength and toughness at elevated temperatures which they attribute primarily to reduction of residual tensile stresses in the as-made material.